2019
DOI: 10.12659/msm.917813
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the Prognosis Predicting Signature for Endometrial Cancer Patient

Abstract: BackgroundNovel biomarkers provide clinicians more critical information on tumor genetic features and patients’ prognosis. Here, we aimed to establish prognosis-predicting signatures for endometrial carcinoma (EC) patients based on the miRNA information.Material/MethodsThe Cancer Genome Atlas (TCGA) website was available for dataset extraction. Prognosis-associated miRNAs were generated by univariate Cox regression test. Online websites were used to predict the targeted genes of these enrolled miRNAs. The miRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In multivariate analyses, not only was a high P53 expression detected to be associated with relapse, but ER and FIGO stage were also independent factors affecting prognosis, which was consistent with other reports 19‐21 . Although histological type and grade, myometrial invasion, cervical stromal invasion, postoperative adjuvant therapy, and the expression of PR and Ki‐67 had not shown a significant correlation with relapse in multivariate analysis, their predictive value for relapse in endometrial cancer cannot be denied.…”
Section: Discussionsupporting
confidence: 88%
“…In multivariate analyses, not only was a high P53 expression detected to be associated with relapse, but ER and FIGO stage were also independent factors affecting prognosis, which was consistent with other reports 19‐21 . Although histological type and grade, myometrial invasion, cervical stromal invasion, postoperative adjuvant therapy, and the expression of PR and Ki‐67 had not shown a significant correlation with relapse in multivariate analysis, their predictive value for relapse in endometrial cancer cannot be denied.…”
Section: Discussionsupporting
confidence: 88%
“…The prognostic evaluation of EnCa has always been a hot topic for concerned scholars. Construction of scoring models will contribute to quantification of the prognostic evaluation criteria, and an increasing number of studies are successfully establishing precedents in this regard [22][23][24]. In the current research, a series of systematic bioinformatics analyses were conducted, ultimately leading to the development of a novel 13-lncRNA signature associated with the clinical outcome of EnCa patients; this signature included AL080317.2, ERICH6-AS1, AC016877.3, MCCC1-AS1, AC120053.1, AC138932.5, ZNF433-AS1, SCARNA9, DBH-AS1, AL157932.1, AC073046.1, POC1B-AS1, and AP003419.3.…”
Section: Discussionmentioning
confidence: 99%
“…The first attempts to use the miRNA profile to predict OFS, PFS, and RFS have also been made [ 40 , 41 , 42 ]. Tang and colleagues used TCGA data to establish a prognosis signature based on the hazard ratio (HR) of each miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…With this signature, the authors showed that patients in a high-risk group have poorer OS compared to the low-risk group. Unfortunately, this classification rule was less efficient than the clinical stage but was superior to histological type or neoplasm histological grade [ 42 ]. The potential of miRNA profile in predicting the course of the disease is high, however, the use of miRNA-based stratification should be assisted with genomic subtyping.…”
Section: Discussionmentioning
confidence: 99%